Biomechanical correlates of sequential drinking behavior in aging. Issue 1 (14th July 2020) - Cock, Charles; Omari, Taher I.; Burgstad, Carly M.; Thompson, Alison; Doeltgen, Sebastian H.
Abstract: Background: The timed water swallow test (TWST) is a test of sequential swallowing where a measured volume is ingested as quickly as comfortably possible. We undertook a study of the biomechanics underpinning the TWST in healthy young and older participants. Methods: Thirty healthy volunteers underwent high‐resolution impedance manometry (MMS; Unisensor, 2.7 mm diameter, 32 pressure sensors, 16 impedance segments). Participants were asked to drink 150 mL, 0.9% normal saline solution rapidly. Swallowing biomechanics and bolus flow characteristics were assessed using pressure‐flow analysis and compared using t test and Fisher's exact test with significance as P < .05. Key Results: Older participants (n = 18; 76 ± 11 years) took longer to complete the TWST (21.2 ± 2.5 vs 9.2 ± 1.0 seconds; P < .001) and displayed reduced volume per swallow (16.6 ± 1.3 vs 27.8 ± 2.9 mL; P < .001) compared to younger participants (n = 12; 29 ± 5 years). Two distinctive pharyngeal swallowing patterns were observed: (a) a single rapid sequence of swallows with or without a clearing swallow (Pattern I) or (b) multiple, shorter sequences interrupted and/or interspersed with single swallows or breaks (Pattern II). Some older participants showed biomechanical evidence of upper esophageal sphincter restriction (n = 7) or impaired deglutitive inhibition (n = 7), associated with the more prolonged Pattern II (TWST duration 30.1 ± 1.5 vs Pattern I 11.9 ± 1.5 seconds; P < .001). Conclusions and Inferences: Healthy older participants had an increased duration of TWST, suggesting a need to adapt normative values for this population. Rapid sequential swallowing was associated with evidence of UES restriction and impaired deglutitive inhibition in some older participants. Abstract : Pressure‐flow analysis displays upper esophageal bolus flow, which allows for an accurate determination of time taken to drink a measured volume. Older participants (76±11 years) took markedly longer compared to younger participants (29±5 years).